Isolated Axillary Lymph Node Metastasis from Serous Ovarian Cancer. (24th October 2012) - Goyal, Hemant; Mattoo, Vijay K.; Singla, Umesh
Abstract : A 68-year-old female with past medical history of stage IIIc serous ovarian cancer after cytoreductive surgery and adjuvant chemotherapy came to clinic for regular follow-up visit. Physical examination was completely normal except for an isolated left axillary lymph node enlargement. Patient's abdominal sonogram and CT scan of abdomen and pelvis did not show any other new metastasis. Surgical excisional biopsy of the lymph node was performed and pathology revealed features of metastatic serous ovarian carcinoma.